Communication Strategies Used By The Eight Grade Students In Speaking Class Of Mts Negeri Miri In Academic Year 2015/2016 - Mastuti, Indria Sri; , Dr. Anam Sutopo, M.Hum; , Mauly Halwat Hikmat, Ph.D (2015)
The students have a purpose in learning a language especially English that they want to be able in speaking. However, in the practice, some communication problem occured. The existence of communication problems are coped by using some communication strategies. This study was an attempt to obtain data on the types of communication strategies used by the students while speaking, to handle their difficulty in speaking performance. In order to obtain those data, a descriptive qualitative research design was used in this study. The subject of the study was class VIII A which consist of 26 students in MTs Negeri Miri in the academic year 2015/2016. Moreover, the primary data of this study were communication strategies appeared in the sudents‟ utterances. To obtain the data,observation, interview, field notes and recording were employed. In addition, Dornyei and Scott‟s taxonomy was used to classify the data. The results show that during implementation of retelling story, the students used some communication strategies which support Dornyei and Scott‟s taxonomy: (1) message abandonment, (2) topic avoidance, (3) circumlocution, (4) approximation, (5) use of all-purpose words, (6) word coinage, (7) use of non-linguistic means, (8) literal translation, (9) foreignizing, (10) code switching, (11) appeal for help, and (12) fillers or hesitation. Moreover, the frequencies of using are as follows: The dominant type of communication strategies used by the eight grade students in MTsN Miri is filler or hesitation type with 49,19 % or 152 utterances. The second is appeal for help with 14,24 % or 44 utterances. The third is message abandonment with 13,27 % or 41 utterances, the fourth is use of non-linguistic meanswith 5,50 % or 17 utterances. The fifth is foreignizing with 4,53 % or 14 utterances, the sixth is topic avoidance with 3,88 % or 12 utterances. The seventh is use of all purpose words with 2,91 % or 9 utterances, the eight is circumlocution and code switching with 2,27 % or 7 utterances because both have the same amount. The ninth is approximation with 0,97 % or 3 utterances. The tenth is word coinage with 0,65 % or 2 utterances and finally, the lowest number goes to literal translation with 0,32 % or 1 uttreance only. In addition, there are three reasons why the students employed communication strategies in their retelling story: first, because they wanted their speaking to run well or communicatively because most of them still have limited vocabularies; second, the students need time to think because they tried to memorize the next words to say; the third, they need help from other friends to give a clue of the next words. Hopefully, this research result can be used for the teacher to give knowledge about communication strategies and for the students to develop their speaking skill by using more communication strategies